Techno-economic assessment of gas engine power plants penetration in a power grid - Adelhard Beni Rehiara; Frederik Haryanto Sumbung (International Journal of Applied Power Engineering (IJAPE), 2026)
This paper presents a techno-economic assessment of integrating engine power plants into a power grid, using the snake optimization (SO) algorithm to solve the multi-objective optimal power flow (OPF) problem. The study focuses on four key objectives: minimizing fuel costs, reducing voltage deviation, enhancing voltage stability, and minimizing active power losses. Simulations conducted on the 38-bus of Manokwari grid system demonstrate that the SO algorithm significantly improved performance in all areas. Fuel costs were reduced to 2.003 million USD/h while maintaining a stable voltage profile. Voltage deviation was reduced to 0.5577 p.u., ensuring better voltage consistency across the grid. Voltage stability was enhanced with a minimized Lmax value of 0.0200 p.u., and active power losses were reduced to 0.3423 MW, reflecting a notable increase in system efficiency. These findings demonstrate the effectiveness of integrating gas engine power plants, which led to noticeable improvements in operational efficiency and grid stability.